Influence of economic factors on the environment in countries with different levels of development. (February 2020) - Filimonova, I.V.; Provornaya, I.V.; Komarova, A.V.; Zemnukhova, E.A.; Mishenin, M.V.
Abstract: The pattern of development of the economies of Europe and the world in recent decades is a focus on sustainable development. In accordance with the declaration of the United Nations Conference of 1992, sustainable development is defined as ≪ equitable meeting the needs of present and future generations in the areas of development and the environment ≫ and is established as one of the goals of government policy in many countries of the world. The concept of sustainable development solves the problem of choosing between achieving a high rate of economic growth and maintaining a clean environment. The purpose is to study and quantify the impact of economic factors on the state of the environment in countries with different levels of development. The study revealed existing patterns and built new mathematical models that can be used in strategic planning, allow predicting the possible environmental consequences of economic growth in Europe and the world. The use of the proposed models allows not only to assess the impact of economic growth on the environment in retrospect, but also to highlight the most significant factors contributing to the reduction of environmental pressure in the future.